PENGARUH PERILAKU BELAJAR DAN KECERDASAN EMOSIONAL TERHADAP STRESS KULIAH DAN PRESTASI BELAJAR MAHASISWA POLITEKNIK NEGERI BALI - I Wayan Edi Arsawan (Soshum: Jurnal Sosial dan Humaniora, 2013)
The purpose of this research was to determine the effect of learning behavior and emotional intelligence Bali State Polytechnic students against stress and achievement. This type of research used is descriptive qualitative, method of collection through interviews, questionnaires and observation, analysis techniques by using a Likert scale to identify each of the variables associated with behavioral learning, emotional intelligence, stress and college academic achievement Bali State Polytechnic students by using analysis pathways. T h e results is 1) the learned behavior partially negative influence on college stress the value and influence coefficient -0.084 with 20.5%. influence This means that the negative effect on learning behavior strees college. If the negative behavior of the stress lectures learning will increase and vice versa if a positive learning attitude will decrease the stress college too. 2) Emotional intelligence significantly influence the stress variable course with a large coefficient of 0.267 with the effect of 49.2%. This means that if a higher emotional intelligence Bali State Polytechnic students study the stress will decrease indicating that reducing stress levels will require a higher emotional intelligence. 3) Stress lectures significant effect on the achievement of students with the coefficient of -0.154 with a large effect was 7.7%. Sign (-) means negative that if Bali State Polytechnic students increased stress the achievements of college will decrease and if the stress has decreased the achievement will increase. 5) learning behavior significantly negative effect on student academic achievement through college stress variable with a value totaling coefficient -0.154, while emotional intelligence variable significant positive effect on academic achievement through college stress.